2023
DOI: 10.1002/acn3.51782
|View full text |Cite
|
Sign up to set email alerts
|

“Brain age” predicts disability accumulation in multiple sclerosis

Abstract: Objective Neurodegenerative conditions often manifest radiologically with the appearance of premature aging. Multiple sclerosis (MS) biomarkers related to lesion burden are well developed, but measures of neurodegeneration are less well‐developed. The appearance of premature aging quantified by machine learning applied to structural MRI assesses neurodegenerative pathology. We assess the explanatory and predictive power of “brain age” analysis on disability in MS using a large, real‐world dataset. Methods Brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…The brain-age paradigm offers a window into this problem and has been previously used to characterize neurodegeneration in multiple sclerosis due to its sensitivity to brain ageing-like patterns. 57,24,25 In line with previous studies, our results confirmed that, when observed through the lens of healthy ageing, the brains of PwMS look older than normal (around eight years on average), suggesting that at least some of the disease-related variance in brain structure can be effectively modelled in terms of premature/accelerated brain ageing.…”
Section: Discussionsupporting
confidence: 91%
“…The brain-age paradigm offers a window into this problem and has been previously used to characterize neurodegeneration in multiple sclerosis due to its sensitivity to brain ageing-like patterns. 57,24,25 In line with previous studies, our results confirmed that, when observed through the lens of healthy ageing, the brains of PwMS look older than normal (around eight years on average), suggesting that at least some of the disease-related variance in brain structure can be effectively modelled in terms of premature/accelerated brain ageing.…”
Section: Discussionsupporting
confidence: 91%